Studies on the effect of sintering conditions on the magnetostriction characteristics of cobalt ferrite derived from nanocrystalline powders - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Journal of the European Ceramic Society, 2014)
The effect of sintering conditions on the magnetostriction characteristics of sintered cobalt ferrite derived from nanocrystalline powders is studied. It is observed that the magnetostriction coefficient as well as the slope of the magnetostriction as a function of field depends on the microstructure of the sintered product. There is a direct correlation between the magnetostriction characteristics and density as well as porosity of the sintered products. Intragranular pores are found to be strongly influencing the magnetostriction characteristics. Similarly, correlation is found between the magnetostriction parameters and the Curie temperature, indicating the role of cation distribution which affects the magnetic anisotropy. Sintering the compacts made from nanocrystalline powders at 1450 degrees C for a very short duration is found to give high values of magnetostriction coefficient. However, higher values of magnetostriction at low magnetic fields are obtained for samples sintered at lower temperatures for longer duration and having relatively lower density. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cobalt ferrite; Magnetostriction; Microstructure; Nanocrystalline; Sintering